2015
DOI: 10.3384/diss.diva-115598
|View full text |Cite
|
Sign up to set email alerts
|

Guided Regeneration of the Human Skin : in vitro and in vivo studies

Abstract: "Jag förstår att mamma håller på med något viktigt men är det inte bara att sätta på ett plåster?"Elvin åtta år SUPERVISOR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 117 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…In the exploratory pilot case study, the 24 hour increase in erythema after patching we observed was consistent with other studies, for instance that of Nyman 24 , using the TiVi system after hyaluronic acid or sodium chloride provocation. Nyman proposed that cells at 24 hours were responding to wound trauma in a pro-inflammatory manner, which supports the increasing erythema score ( Figure 5) over that time period returning to baseline after 14 days.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…In the exploratory pilot case study, the 24 hour increase in erythema after patching we observed was consistent with other studies, for instance that of Nyman 24 , using the TiVi system after hyaluronic acid or sodium chloride provocation. Nyman proposed that cells at 24 hours were responding to wound trauma in a pro-inflammatory manner, which supports the increasing erythema score ( Figure 5) over that time period returning to baseline after 14 days.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…In this case study, we used tissue viability imaging (TiVi), which quantifies the erythema induced in superficial capillaries of skin through subsurface polarised light spectroscopy 21 . TiVi has been used to examine cutaneous microcirculation after cryotherapy 22 , heat therapy 21 , drug delivery through iontophoresis 23 , hyaluronic acid and histamine provocations 24 , but not in relation to microneedle mediation. It is hypothesised that this method may provide valuable data because of the potential of pro-inflammatory stimulation induced by highdensity microneedles 25 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This shows that addition of curdlan to PVA slows the degradation process since the former is resistant to hydrolysis . A longer degradation time might be beneficial since the scaffold can maintain the physical properties of the dermis for considerable amount of time in the case of large burn wounds …”
Section: Resultsmentioning
confidence: 98%
“…[31] A longer degradation time might be beneficial since the scaffold can maintain the physical properties of the dermis for considerable amount of time in the case of large burn wounds. [32]…”
Section: In Vitro Swelling and Degradation Studiesmentioning
confidence: 99%
“…Human genes MSX-1, MSX-2, and MOX-1 are differentially expressed in skin development. Additionally, fetal repair without scarring is associated with decreased expression of HOXB13 and increased PRX-2 [47]. Thus, PRX-2 activation is important for stimulating dermal formation.…”
Section: Genesmentioning
confidence: 89%